Is Call Auction Efficient for Better Price Discovery? - Jena, Sangram Keshari; Dash, Ashutosh (Asian Journal of Empirical Research, 2015)
The National Stock Exchange of India (NSE) implemented call auction trading mechanism on18 October 2010 in its opening session for better opening price discovery. Excess volatility is observed at the opening due to uncertainty surrounding the fundamental value following the overnight non- trading hours. Therefore, the objective of call auction during a pre-open session is to minimize the market price fluctuations which subsequently leading to better price-discovery. GARCH (1, 1) model, after accounting for the impact of overnight information, noise and previous day’s closing market, found that the unconditional volatility at the opening, in 16 out 26 stocks, is reduced following the introduction of pre-open call auction session. In absence of spread in call auction market Lee (2008), the lower volatility could be attributed to higher depth in terms of more outstanding orders at the best bid and ask price, given the strong endogeneity amongst spread, depth and volatility. Consequently it is the depth in call market which could lower the price volatility for better price discovery.